The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.sleep.2017.11.102
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms are more common among short sleepers independent of obesity

Abstract: Introduction Sleep length has been associated with obesity and various adverse health outcomes. The possible association of sleep length and respiratory symptoms has not been previously described. The aim of this study was to investigate the association between sleep length and respiratory symptoms and whether such an association existed independent of obesity. Methods This is a multicentre, cross-sectional, population-based study performed in 23 centres in 10 different countries. Participants (n=5079, 52.3% m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Several studies have suggested that asthmatic patients are known to have troublesome nights, including not sleeping, waking up in the middle of the night, and early in the morning [ 7 ]. Recently, a study including a large sample size of approximately 5,000 patients from 10 European countries concluded that nasal and respiratory factors are correlated with a short duration of sleep (less than six hours) [ 13 ]. Disturbed sleep could potentially lead to drowsiness during the day.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that asthmatic patients are known to have troublesome nights, including not sleeping, waking up in the middle of the night, and early in the morning [ 7 ]. Recently, a study including a large sample size of approximately 5,000 patients from 10 European countries concluded that nasal and respiratory factors are correlated with a short duration of sleep (less than six hours) [ 13 ]. Disturbed sleep could potentially lead to drowsiness during the day.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, poverty is a contributing factor for aggravated asthma symptoms among children [ 29 , 30 ]. Behavioural aspects such as chronotype and sleep pattern are the new additions to the list of asthma modulators [ 31 , 32 ]. Asthma symptoms are synergistic to circadian rhythm; that is, the symptoms get worse in the last part of the night or in the early morning compared to the rest of the day [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%